Finansial Performances and Characteristics:Comparisons of U.S Multinational and Domestic Firms - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
This study examines financial performances and characteristics of U.S. multinational and domestic firms. Michel and Shaked (1986) provide empirical results using the 1973-1982 period. Their study shows that domestic firms have significantly superior risk-adjusted, market performances compared to multinationalfirms performances. However, whether these results still apply to the current conditions is an interesting question because of the changes in economic condition and stock market laws and regulations. Contrary to the expectation, the empirical results show that risk-adjusted, market based performances of multinational firms outperform those of domestic firms. In addition, this study also shows that for multinational firms, quick ratios, return on assets, inventory turnovers, and capitalization ratios are key variables to monitor. For domestic firms, return on assets, market-to-book ratios, and dividend payout ratios are key variables to monitor.